The Effect of Accounting Knowledge, Accounting Training, and Business Experience on the Use of Accounting Information (Empirical Study of MSMEs in Boyolali) - Oktaviyanto, Ryan Funky Wahyu; Sasongko, Noer (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of accounting knowledge, accounting training, and business experience on using accounting information (an empirical study on MSMEs in Boyolali). This research is quantitative with a descriptive approach. The population in this study was all MSMEs in Boyolali. The sampling technique in this study. Using purposive sampling. The number of samples in this study was 100 respondents. This study uses primary and secondary data. The data collection method used in this research is distributing questionnaires via Google Forms. The data analysis technique in this study uses validity test, reliability test, normality test, multicollinearity test, and heteroscedasticity test. The results of this study show that accounting knowledge affects the use of accounting information. Accounting training has no significant effect on the use of accounting information. Business Experience has a significant effect on the Use of Accounting Information.